2019
DOI: 10.1080/13825585.2019.1604941
|View full text |Cite
|
Sign up to set email alerts
|

Age doesn’t matter much: hybrid visual and memory search is preserved in older adults

Abstract: We tested younger and older observers' attention and long-term memory functions in a "hybrid search" task, in which observers look through visual displays for instances of any of several types of targets held in memory. Apart from a general slowing, search efficiency did not change with age. In both age groups, reaction times increased linearly with the visual set size and logarithmically with the memory set size, with similar relative costs of increasing load (Experiment 1). We replicated the finding and furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 95 publications
7
17
0
Order By: Relevance
“…We recently examined age differences in hybrid search. While there was evidence of general age-related slowing, we demonstrated similar RT × set size functions for younger and older adults: The relative costs of adding distractors to the display and adding targets to the memory set were similar for both age groups (Wiegand & Wolfe, 2020 ), even up to high set sizes (64 items; Wiegand et al, 2019 ). This suggests no qualitative age differences in processing in the standard task version, where targets from the memory set appear in random order across trials.…”
Section: The Present Studysupporting
confidence: 55%
“…We recently examined age differences in hybrid search. While there was evidence of general age-related slowing, we demonstrated similar RT × set size functions for younger and older adults: The relative costs of adding distractors to the display and adding targets to the memory set were similar for both age groups (Wiegand & Wolfe, 2020 ), even up to high set sizes (64 items; Wiegand et al, 2019 ). This suggests no qualitative age differences in processing in the standard task version, where targets from the memory set appear in random order across trials.…”
Section: The Present Studysupporting
confidence: 55%
“…These results are consistent with recent studies highlighting an absence of qualitative visual search differences in older adults (Wiegand et al, 2019; Wiegand & Wolfe, 2020). Although Madden et al (2004) similarly concluded that top-down contributions to visual search were preserved as a function of age, their results actually showed an exacerbated effect of their manipulation of the predictive value of the singleton being the target for older adults.…”
Section: Discussionsupporting
confidence: 93%
“…These authors replicated previous literature with younger adults that adding items to the search display (i.e., set-size) led to a linear increase in RT, whereas adding items to the memory set led to a logarithmic increase in RT. Wiegand and Wolfe (2020) observed this pattern in older adults as well. Across the three experiments, beyond a generalised slowing for older adults, there was no evidence of qualitative differences in search slopes for younger versus older adults (Wiegand & Wolfe, 2020).…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Older adults are often slower and less accurate than are younger adults in performing visual-search tasks, suggesting an age-related decline in attentional functioning 9 , 10 . The slope of RT and display-size function is typically higher for older adults than for younger adults 11 , 12 . When the visual target is a featural singleton, however, older adults typically exhibit independence between RT and display size, indicating a highly efficient search despite slower overall RT 13 , 14 .…”
Section: Introductionmentioning
confidence: 97%